Effect of Air and Steam on the Performance of Syngas Yield Using Downdraft Gasification Method - Shamsuddin, Siti Syafrina Nurhidayah; Samiran, Nor Afzanizam (Progress in Engineering Application and Technology, 2021)
Considering shifts in the global climate, there is an opportunity to diversify from fossil fuels as part of measures to minimize greenhouse gas emissions. As an energy source, biomass has the potential to generate sustainable energy and fuels and to contribute to a cleaner future. Utilizing biomass as a carbon dioxide neutral organic source in an integrated system effectively produces useful goods and reduces waste and non-renewable resource usage. Gasification, the preferred method for biomass conversion into fuel gas, offers greater electrical efficiencies than combustion, making it possible to use the syngas produced by the gasification process to generate clean energy. In addition, syngas can also be used for ammonia and methanol production, thus reducing their respective natural gas dependencies. This study will detail the biomass gasification process considering the type of gasifier and various gasifying agents. To achieve this aim, an ANSYS Fluent simulation model is developed to analyze the effect of various gasification agents on the performance of syngas yield and temperature distribution. The comparative analysis between the single-stage and two-stage downdraft reactor is performed to study the influence of air as gasifying inlet corresponding in comparison with steam and air for primary and secondary ports of gasifying inlet. Based on the results and discussion, the two-stage downdraft reactor utilizes the maximum production rate of syngas yield composition with temperature distribution in the range of 350-2000 K along the gasifier. This shows the increase in temperature has a positive impact on the quality of syngas generated and the performance of the gasification process.